Pengaruh Sarana Audiovisual Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di Madrasah Aliyah Al-Islamic Amalia Kota Tebing Tinggi - Lubis, Azlam Zul Ashfi; Siregar, Chairuddin; Muliatno (STAI Tebing Tinggi Deli, 2024)
The purpose of this study is to analyze the influence of media (audio visual) on student learning achievement in the subject of Akidah Akhlak at Madrasah Aliyah Al-Islamic Amalia Tebing Tinggi City; to find out whether there is a difference in learning achievement between students who use audio visuals and those who do not. Educational facilities are everything that supports the teaching and learning process in an educational environment. These facilities include various facilities and equipment used to support educational activities, such as classrooms, laboratories, libraries, stationery, books, computers, and sports facilities. This study is included in quantitative research. The data collection techniques used by the researcher are Written Tests and questionnaires. The results of the study indicate that the Availability and Quality of Facilities (Audiovisual) at Madrasah Aliyah Al-Islamic Amalia Tebing Tinggi City are included in the moderate category, which is in the interval 33.04 - 39.07 with an average value of 36.06. This is because Madrasah Aliyah Al-Islamic Amalia Tebing Tinggi City is one of the newly established Madrasahs in Tebing Tinggi City so that the Availability and Quality of Facilities are not classified as high. In the experimental class, there was an increase in the average value from 52.41 to 75.24. There was a change of 22.83 in the experimental class. Likewise, in the control class, the average value increased from 58.11 to 63.44, which was 5.33. This means that the increase in the average value before and after treatment in the experimental class was higher than in the control class. Based on hypothesis testing of the posttest data of the experimental group in the paired samples test output table above, it is known that the Sig. (2-tailed) value is 0.000 <0.05, so H0 is rejected and Ha is accepted. So it can be seen that there is an average difference between the learning outcomes of the pretest and posttest, which means that there is an influence of the media (audio visual) on students' learning achievement in the subject of Aqidah Akhlak at Madrasah Aliyah Al-Islamic Amalia, Tebing Tinggi City.